Between "Holy War" and the "Crusade"? (Polis (Santiago), 2018)
In reference to the Twin Towers attack, the author delineates the characteristics of political terrorism and declares as its central objective to seal of democratic space. Underlying to this strategy is the idea that it will lead to political polarization which will force victims and critics of power to follow those who lead terrorism. This, he says, in detriment of the dominated, because on one side, the dominant response is almost always state terrorism, which traps and destroys leaders and members of the opposing social groups. It postulates that terrorism should be judged and punished as all criminal acts, but also avoided, prevented and disabled. He then analyzes the thesis of the clash of civilizations, and Bush’s strategic answer.
Keywords: terrorism; twin towers; war of civilizations; Bush